TAMI-21. MALIGNANT GLIOMAS REMODEL FUNCTIONAL NEURAL CIRCUITS THROUGH PARACRINE SIGNALING WHICH CONFERS A NEGATIVE PROGNOSIS. (9th November 2020) - Krishna, Saritha; Choudhury, Abrar; Ni, Lijun; Seo, Kyounghee; Kakaizada, Sofia; Findlay, Anne; Lee, Anthony; Sudharshan, Rasika; Cao, Caroline; Venkatesh, Humsa; Vogel, Hannes; Phillips, Joanna; et al.
Abstract: BACKGROUND: Unlike cancers affecting many solid organs, gliomas exist within the context of complex neural circuitry. It remains unknown whether glioma-neuron interactions play a role in maintaining functional circuits underlying cognition. We test the hypothesis that malignant gliomas remodel functional circuits through glioma-neuron interactions. METHODS: Using language processing as a model for functional circuit dynamics, we enrolled 53 patients with dominant hemisphere IDH-wild-type glioblastoma. Task related circuit dynamics were measured using electrocorticography. Magnetoencephalography measures of functional connectivity identified intratumoral connectivity (HFC) and suppressed connectivity (LFC) regions. Primary patient samples and cultures from HFC and LFC-sites were assessed by single-cell RNA sequencing, pre/post-synaptic marker expression, cocultured with murine hippocampal neurons, and induced neuron organoids. Hippocampal tumor xenografts were created. Language/survival statistics were performed to correlate with functional connectivity measures. RESULTS: Speech production evokes neuronal population spikes within the entire area of tumor-infiltrated cortex, far beyond the cortical territory normally involved in expressive language. Primary patient samples from HFC-regions are enriched for glioblastoma cells with a synaptogenic profile as characterized by pre-and post-synaptic marker expression at both tissue and cellular levels. RNA-sequencing and proteomic analyses from HFC samples revealed a neurogenic signature including thrombospondin-1 originating from glioma cells in HFC-regions and non-tumor astrocytes in LFC-regions. HFC xenografts demonstrated increased total number of synapses. Importantly, when compared with gliomas without intratumoral functional connectivity, connected gliomas have worse language task performance (r= -0.54, p=0.03) and shorter OS (medianOS-64 weeks compared with 107-weeks, p=0.04). CONCLUSION: Glioma infiltrated regions generate task-relevant neural responses, with speech production evoking neuronal activity throughout tumor-involved cortex in the dominant hemisphere. An enriched population of synaptogenic glioma cells are organized within functionally connected intratumoral regions and this confers negative functional and survival outcomes. Together, these findings indicate that malignant gliomas can functionally remodel neural circuitry, thereby impairing neurological function and promoting tumor progression.